Determination and modeling of binary and ternary solid-liquid phase equilibrium for the systems formed by 1, 8-dinitronaphthalene and 1, 5-dinitronaphthalene and N-methyl-2-pyrrolidone. (October 2016) - Xie, Yong; Du, Cunbin; Cong, Yang; Wang, Jian; Han, Shuo; Zhao, Hongkun
Graphical abstract: Highlights: SLE formed by 1, 5 and/or 1, 8-dinitronaphthalene and NMP was determined. The binary and ternary phase diagrams were constructed. The phase diagrams were correlated and calculated using thermodynamic models. Abstract: The solubility of 1, 8-dinitronaphthalene and 1, 5-dinitronaphthalene in N -methyl-2-pyrrolidone at (293.15–343.15) K and the mutual solubility of the ternary 1, 5-dinitronaphthalene + 1, 8-dinitronaphthalene + N -methyl-2-pyrrolidone mixture at (313.15, 328.15 and 343.15) K were determined experimentally using the isothermal saturation method under atmospheric pressure (101.2 kPa). The solubility of 1, 8-dinitronaphthalene in N -methyl-2-pyrrolidone is larger than that of 1, 5-dinitronaphthalene. Three isothermal ternary phase diagrams were built according to the measured mutual solubility data. In each ternary phase diagram, there were one co-saturated point, two boundary curves, and three crystalline regions. Two pure solids (pure 1, 8-dinitronaphthalene and pure 1, 5-dinitronaphthalene) were formed in the ternary system at a given temperature, which were identified by Schreinemaker's method of wet residue and powder X-ray diffraction (PXRD) pattern. The crystallization region of 1, 8-dinitronaphthalene was smaller than that of 1, 5-dinitronaphthalene at each temperature. The modified Apelblat equation, λh equation, NRTL model and Wilson model were used to correlate the solubility of 1, 8-dinitronaphthalene and 1, 5-dinitronaphthalene in N -methyl-2-pyrrolidone; and the NRTL and Wilson models were employed to correlate and calculate the mutual solubility for the ternary 1, 5-dinitronaphthalene + 1, 8-dinitronaphthalene + N -methyl-2-pyrrolidone system. The largest value of root-mean-square deviation ( RMSD ) was 20.34 × 10 −4 for the binary systems; and 7.38 × 10 −3 for ternary system. The calculated results via these models are all acceptable for the binary and ternary solid-liquid phase equilibrium.